Phylogenetic and Computational Structure-Function Studies of ?-1,4-Glucosidase (Maltase) From Baker’s Yeast (Saccharomyces cerevisiae) (Biological Sciences - PJSIR, 2008)
Study, through blasting, cladogenesis, multiple sequence alignment and protein homology modeling, ofa,1,4 glucosidase from S. cerevisiae YJM789, showed the presence of different paralogues and orthologues of maltase in different genera of fungi and prokaryotes. The sequences of glucosidases contained 4 characteristic consensus regions. In the tertiary structure (modelled) of Baker’s yeast maltase, all the residues of consensus region were congregated in the central region of the folded protein, rendering the formation of catalytic groove. On the basis of the orientation and spatial location of residues in catalytic groove, Asp200 is proposed to be the second substrate-binding site.